Response of upland rice variety to plant population under the low land agro-ecology of Bench Sheko Zone, South-west Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Plant population has a strong influence on rice yield. A field experiment was conducted during the 2017 and 2018 main cropping seasons at Guraferda district in Bench Sheko Zone, Southwest Ethiopia. The objective of this study was to determine the optimum plant population and appropriate variety on grain yield and yield components of upland rice. The experiment was carried out using RCBD with three replications. Five levels of plant populations (60, 80, 100, 120, and 140 kg ha-1) and three levels of genotypes (Nerica-4, Suparica-1, and Local check) were studied. The main effect of plant population and variety had significant (p